Studies of effector molecules exerting autonomous and nonautonomous influence of T lymphocyte apoptosis under the conditions of in vitro “cell neighborhood” in healthy people and patients with rheumatoid arthritis - T. Ya. Abramova; E. A. Blinova; E. A. Pashkina; L. V. Grishina; N. A. Ilina; O. A. Chumasova; A. E. Sizikov; V. A. Kozlov (Медицинская иммунология, 2022)
Cellular homeostasis in the body is known to be maintained by the processes of cell proliferation and death, whereas apoptosis is the most frequent and physiological, “silent” mechanism of cell elimination. It has been currently shown that the process of apoptosis traditionally considered an autonomous event, has a pronounced non-autonomous effect on migration, proliferation, and death of the neighboring cells. This work was based on the data on impaired programmed death of mononuclear cells from the patients with rheumatoid arthritis (RA) leading to the evolving autoimmune inflammation. The aim of this study was to evaluate effector molecules exerting autonomous and non-autonomous influence of T cell apoptosis under the conditions of “cell neighborhood” in cell cultures of healthy people and RA patients. The studies were performed with blood samples of RA patients and healthy women of comparable age. These experiments were performed in order to assess the levels of main molecules mediating the in vitro receptor and mitochondrial apoptosis of T lymphocytes. In previous studies, using the original “cell neighborhood” model, no differences were found in parameters of early and late activation apoptosis between the groups of donors and RA patients. At the same time, 1-week incubation in apoptotic cultures of the patients was followed by significantly increased number of viable cells carrying the proliferation marker Ki-67. Different results of in vitro apoptosis induction in cultures under similar conditions of “cell neighborhood” in healthy people and patients with RA have revealed the importance of main effector molecules of apoptosis in the studied groups. In this study, we have revealed low potential of the receptor pathway for apoptosis activation in healthy people, due to suppression of TNFα production during cell incubation under the conditions of “cell neighborhood”, and in RA patients due to initially low TNFα in supernatants which did not change over time and in various incubation variants, along with low content of initiating caspase 8 in both groups. Significant suppression of effector molecules of mitochondrial pathway of apoptosis activation, i.e., Bcl-2 anti-apoptotic factor and p53 transcription factor was detected in cultures of apoptotic cells, as well as mixtures of proliferating and apoptotic cells under the conditions of “cell neighborhood” in RA patients. The amounts of these molecules did not change in healthy persons. At the same time, no differences in these molecules were found between individual variants of cell cultures from the patients with RA and healthy people. The both studied groups were characterized by a significant activation of IL-4 and IL-6 production, i.e., the cytokines with autonomous and non-autonomous protective and reparative properties, Hence, one may conclude that high levels of these cytokines had different effects in cell cultures under the conditions of “cell neighborhood”. Incubation of cells from healthy people under suboptimal conditions was associated with maintaining the balance of proliferation and apoptosis, whereas, in cell cultures of RA patients, this balance caused activation of proliferation processes, being accompanied by an increase in the number of living cells in apoptotic cultures.